Analisis Return Saham Dengan Tingkat Inflasi Sebagai Variabel Moderasi Pada Perusahaan Asuransi di Bursa Efek Indonesia - Addina Islamiah, Putri; Ichsanuddin Nur, Dhani (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2025)
This study aims to examine the effect of profitability projected by Return On Equity (ROE), market ratio projected by Price Earning Ratio (PER), dan leverage projected by Debt to Equity Ratio (DER) on stock returns in insurance companies listed on the Indonesia Stock Exchange (IDX) for the period 2020-2023, with inflation as a moderating variable. The research method used is quantitative with the Moderated Regression Analysis (MRA) analysis technique. The research population is insurance companies listed on the IDX during the 2020-2023 period, with samples taken using purposive sampling technique. The data used is secondary data in the form of financial statements dan stock market data. The results showed that profitability can contribute to stock returns. Leverage can contribute to stock returns. Market ratios cannot contribute to stock returns. Inflation cannot strengthen the role of profitability on stock returns. Inflation cannot strengthen the role of profitability on stock returns. Inflation cannot strengthen the role of market ratio on stock returns. Inflation can strengthen the role of leverage on stock returns. The results of this study emphasize the importance of insurance companies managing profitability and leverage optimally, especially in conditions of inflation, which can strengthen the effect of leverage on stock returns. Investors are also advised to consider inflation when evaluating potential stock returns in the insurance sector.